2015
DOI: 10.1016/j.jstrokecerebrovasdis.2015.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of First Recorded “Last Known Normal” Times of Stroke Code Patients

Abstract: Introduction Given the time-sensitivity of thrombolytic therapy, the accurate documentation of last known normal (LKN) time is crucial to ensure optimal management of stroke patients. This study investigates whether a difference exists between preliminary LKN times (first responders and ED practitioners) and revised LKN times (neurology/stroke practitioners), and what potential impact on emergent management of acute stroke this discrepancy may pose. Methods All stroke code patients from UCSD hospitals from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…A recent study reported that the effect of complete reperfusion was retained among patients who underwent mechanical thrombectomy after 6 hours of stroke onset 26 . Onset-to-puncture time may be less critical than puncture-to-reperfusion time with respect to the effect of complete reperfusion, because onset-to-puncture time is sometimes imprecisely determined or documented 27 , while puncture-to-reperfusion time is generally accurately documented.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the effect of complete reperfusion was retained among patients who underwent mechanical thrombectomy after 6 hours of stroke onset 26 . Onset-to-puncture time may be less critical than puncture-to-reperfusion time with respect to the effect of complete reperfusion, because onset-to-puncture time is sometimes imprecisely determined or documented 27 , while puncture-to-reperfusion time is generally accurately documented.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the stroke academic industry roundtable suggested beneficial assessment of (1) neuroprotective agents, (2) IV-tPA, and (3) emerging treatments to decrease reperfusion damage. [12345678910111213141516171819202122232425262728293031] Henninger and Fisher reported that <10% of all patients with AIS receive intravenous thrombolysis and it has been expected that only around 7%–15% of AIS patients are qualified for acute endovascular intervention. [29]…”
Section: Discussionmentioning
confidence: 99%
“…A previous publication by Spokoyny et al ., in 2015, highlighted the necessity for informative package associated to the determination and modification of the certain time of stroke onset, particularly at hospital without stroke expertise. [10]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recently published article by Spokoyny et al (19), to confirm ideal supervision of patients with AIS, the precise documentation of last known normal time seems to be critical. Due to the time sensitivity of thrombolytic therapy, there is need for training in the determination and alteration of the actual time of stroke onset.…”
Section: Discussionmentioning
confidence: 99%